A crossbow system for high-strain-rate mechanical testing - Hamdan, S.; Swallowe, G. M. (Institute of Physics, 1996)
This paper describes a technique developed to measure the uniaxial compressive stress - strain properties of polymers at strain rates appropriate to ballistic and impact events over time scales of tens of microseconds using a crossbow as the projectile launch system. The instrument constructed represents a novel development of existing equipment types. The system is used for compression testing giving stress - strain measurements at strain rates of up to 10⁴ s⁻¹ and over a temperature range of 20-200°c . Stress is calculated directly from a measured force obtained from a calibrated pressure bar. Strain is calculated from the sample displacement measured directly from the intensity reduction of a laser-photodiode unit. The crossbow system provides a relatively inexpensive, reliable and compact alternative to a standard Hopkinson bar.